Competencias TIC de los docentes de matemáticas en el marco del modelo TPACK: valoración desde la perspectiva de los estudiantes. (2019)
The TPACK model intends to group the types of knowledge that teachers need to master in order to integrate ICT into the classroom appropriately. The article aimed to know the students' perception of the ICT competencies of mathematics teachers in the context of the TPACK framework. The study used the quantitative approach with a descriptive-comparative analysis, which allowed to assess the dimensions of knowledge according to the TPACK model. Regarding results, the description of relationships established according to the TPACK knowledge domains enable the comprehension of the level of competencies of the mathematics teacher concerning the integration of ICT in their educational practice. Emphasis was placed on the importance of technological knowledge and its articulation in the classroom within the process of teaching and learning mathematics